Mauritius : 2009 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Mauritius. (IMF Staff Country Reports; Country Report, 2010)
Mauritius' 2009 Article IV Consultation discusses economic developments and policies. Output growth has been slowed from 4.2 percent per year in 2008 to less than 2 percent in 2009, as key drivers of growth have been contracted. Mauritius' growth prospects depend heavily on the global economy, especially the EU. Inflation has fallen to the low single digits as a result of lower global food and commodity prices and the slowdown of the domestic economy. The current account deficit has narrowed as lower imports have more than offset the contraction of external demand.